PROBLEM PENDIDIKAN MULTIKULTURAL DI INDONESIA - Hesti; Kurniansyah; Zulfadli Rizki (PIJAR: Jurnal Pendidikan dan Pengajaran, 2022)
Pluralism of ethnicity, religion, race, class, which should be the capital of development, is often manipulated by the authorities to achieve their political interests. Therefore, when conflicts break out in the region, the state seems to cover up the reality of this diversity in the name of "national unity" or "national stability. This research method uses qualitative research with the type of liberal research. As for data collection, it uses books, journal articles, and websites. relevant to the research title.The results of the research with the analysis of various references state that the societal problems of multicultural education in Indonesia include: diversity of regional cultural identities, shifts of power from the center to the regions, narrow fanaticism, lack of solid nationalism, conflicts of national and multicultural unity , Unequal Economic Prosperity Among Cultural Groups, Low Quality of Educational Facilities and Infrastructure, Unclear Educational Objectives, Incorrect Measurements and Curriculum Mismatches.